Fibrosis score predicts mortality in patients with fibrotic hypersensitivity pneumonitis - Oh, Ju Hyun; Kang, Jieun; Song, Jin Woo (Frontiers in Medicine, 2023)
Background Variable clinical courses make it challenging to predict mortality resulting from fibrotic hypersensitivity pneumonitis (HP). This study evaluated the usefulness of radiologic parameters for predicting mortality in patients with fibrotic HP. Methods Clinical data and high-resolution computed tomography (HRCT) images, which were scored for reticulation, honeycombing, ground glass opacity (GGO), consolidation, and mosaic attenuation (MA) by visual assessment, were retrospectively analyzed in a total of 101 patients with fibrotic HP (all biopsy-proven cases). Fibrosis score was defined as the sum of reticulation and honeycombing scores. Results The mean age of the 101 patients was 58.9 years, and 60.4% were females. During the follow-up (median: 55.5 months; interquartile range: 37.7–89.0 months), the 1-, 3-and 5-year mortality rates were 3.9, 16.8, and 32.7%, respectively. The non-survivors were older and had significantly lower lung function and minimum oxygen saturation during the 6-min walk test than the survivors. The non-survivors had higher scores of reticulation, honeycombing, GGO, fibrosis, and MA on HRCT than survivors. In the multivariable Cox analysis, reticulation, GGO, and fibrosis scores were independent prognostic factors for mortality in patients with fibrotic HP, as well as age. Fibrosis score showed great performance for predicting the 5-year mortality (AUC = 0.752, p < 0.001) and higher mortality was recorded for patients with high fibrosis score (≥12.0%) (the mean survival time: 58.3 vs. 146.7 months, p < 0.01) than those without. Conclusion Our results suggest that radiologic fibrosis score may be a useful predictor of mortality in patients with fibrotic HP.